CALCULATION OF THE DRAINLESS OPERATION MODES OF TYPE «C» VESSEL CRYOGENIC TANKS - A. Yu. Baranov; L. V. Ivanov; A. M. Andreev (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. For autonomous gasification, it is necessary to create river vessels to transport liquefied natural gas and work out the transportation technology. As the most efficient cargo storage system, C-type tanks are selected and operated in a non-drainage mode. Methods. The existing methodology for determining the level of initial filling of the tank does not consider the storage time of liquefied natural gas, which leads to the forced discharge of the formed liquefied natural gas vapors when the maximum allowable overpressure in the tank is reached. When  upgrading a tanker into a transportation vessel for liquefied natural gas, the authors propose to install two C-type tanks on it. The diameter of the  hemispherical covers is 9 m, the length of the cylindrical part of the tank is 20 m. The maximum permissible overpressure inside the tank is assumed  to be 0.65 MPa. The thickness of the thermal insulation is determined from  the overall dimensions of the hold, considering the condition of ensuring a distance between the hull sidewall and the outer insulation layer of at least760 mm. The maximum possible thickness of the thermal layer was 1.1 m. Results. The article proposes a method for determining the optimal tank filling level to achieve a drainless operation mode. The proposed method can achieve the maximum economic efficiency of transportation of liquefied natural gas by eliminating the loss of discharged liquefied natural gas due to long ship crossings and transporting an additional liquefied natural gas  volume for a short changeover. Conclusion. As the pressure of liquefied natural gas vapor increases inside the tank, the saturation temperature of the liquid fraction increases, and its density decreases. Thus, the proportion of the liquid volume is constantly increasing, reducing the vapor space of the container. An increase in the mass of liquefied natural gas vapors combined with a decrease in the steam area volume increases the pressure growth rate. When optimizing the initial tank filling level, the amount of liquefied natural gas that will be forced  to be discharged as steam on long legs is determined. Optimization of the operating mode of type C tanks is possible for cases with any thickness of the insulation layer. When performing such calculations, tables  of optimal filling for any range of legs can be created.